2022
DOI: 10.1038/s42003-022-03040-5
|View full text |Cite
|
Sign up to set email alerts
|

Haploidy in somatic cells is induced by mature oocytes in mice

Abstract: Haploidy is naturally observed in gametes; however, attempts of experimentally inducing haploidy in somatic cells have not been successful. Here, we demonstrate that the replacement of meiotic spindles in mature metaphases II (MII) arrested oocytes with nuclei of somatic cells in the G0/G1 stage of cell cycle results in the formation of de novo spindles consisting of somatic homologous chromosomes comprising of single chromatids. Fertilization of such oocytes with sperm triggers the extrusion of one set of hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…G0/G1 somatic cells, transferred into enucleated MII oocytes, could form a meiotic spindle-chromosomal complex in SCNT oocytes (Lee et al, 2022). A comparable spindle-chromosomal complex to that in intact metaphase oocytes was observed at 2 hours after SCNT.…”
Section: The Formation Of the Meiotic Spindle-chromosomal Complex Fro...mentioning
confidence: 78%
See 2 more Smart Citations
“…G0/G1 somatic cells, transferred into enucleated MII oocytes, could form a meiotic spindle-chromosomal complex in SCNT oocytes (Lee et al, 2022). A comparable spindle-chromosomal complex to that in intact metaphase oocytes was observed at 2 hours after SCNT.…”
Section: The Formation Of the Meiotic Spindle-chromosomal Complex Fro...mentioning
confidence: 78%
“…Reconstructed oocytes were fertilized and then a set of somatic chromosomes was extruded from the cytoplasm to the form of a pseudo-polar body (PPB) (Lee et al, 2022). The remaining somatic and the sperm chromo-somes form two nuclei (2PNs) in the zygote.…”
Section: The Formation Of the Meiotic Spindle-chromosomal Complex Fro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the present study revisited the haploidization of diploid somatic chromosomes using the somatic cell nuclear transfer (SCNT) [ 145 ]. Through it, it was confirmed that meiotic spindles were formed after the transfer of G0/G1 somatic cells into enucleated MII oocytes and succeeded to generate the somatic haploid chromosome ( Figure 7 ).…”
Section: Haploidization In Somatic Chromosomesmentioning
confidence: 99%
“…The embryo with the somatic haploid can then develop and produce live offspring. SCNT: somatic cell nuclear transfer [ 145 ].…”
Section: Figurementioning
confidence: 99%